Political Relationships, Global Financing and Corporate Transparency - Christian Leuz; Felix Oberholzer-Gee (Center for Research in Economics, Management and the Arts (CREMA), 2003)
This study examines the financing choices of firms operating in a weak institutional environment. We argue that in relationship-based systems, global financing and political connections are substitutes: Well-connected firms are less likely to access foreign capital markets because (state-owned) domestic banks provide capital at low cost. Moreover, the additional scrutiny that comes with foreign securities might be at odds with close political ties at home. Using data from Indonesia, we provide strong support for this hypothesis. Firms with close political ties to former President Soeharto are significantly less likely than non-connected firms to have publicly traded foreign securities. We also examine how returns before and during the Asian financial crisis differ between firms with and without foreign securities. The former performed significantly better during the crisis, and their performance advantage increases considerably once we control for a firm's closeness to the Soeharto regime. We show that simple return regressions in earlier work are downward biased if domestic opportunities such as political connections are ignored.
Keywords: P16; G32; G38; K22; K42; M41; G18; 330; Disclosure; Cross listing; Financing choices; Emerging market economies; Asian financial crisis; Indonesia; Cost of capital